LAND USE PLANNING AND LAND EVALUATION OF THE UPPER CATCHMENT AREA OF BATANG HARI RIVER - Azwar Rasyidin (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2005)
The upper catchment of Batang Hari river in this report is define for the areas of Batang Hari at the end point of Batang Hari Irrigation scheme project at the village of Teluk Kayu Putih of district of Tebo of the Jambi Province up to the Twin lake Of Danau Diateh in the inland areas of Batang Hari river. Covered the areas about 695.400ha which divide to the sixth of sub catchment ie; Momong (41.750ha); Bt. Hari (184.340ha); Sangir (128.660ha); Siat about 45.100ha with divided into small catchment of the Siat river tributaries which main Siat tributary (32.800ha), Piruko/Palangko tributary (7.300ha), Mimpi tributary (5.000ha); Jujuhan (187.300ha) and Pangian (108.250ha). Detail of information showed at Fig. 1 and table 1. Except of sub catchment of Momong, Jujuhan and Pangian, three tributaries already used for irrigation water. The new construction of dam for irrigation scheme are located after joint tributaries of Sangir which flow from Lake Rawa Banto of Mount Krinci and Batang Hari tributary which flow from Lake DiAteh. The length of each main stream Sangir and batang Hari is 118 km and the total length of tributaries conducted of both tributaries is 603km. Based on the hydrological point of view Sangir tributaries is important because these areas high in the annual rainfall. The amount of precipitation of station Liki, Pinang Awan and lubuak Gadang has recorded more than 4000mm annually. The areas could be grouped to the Zone Agroclimatic A of Oldelman. Batang Hari tributaries which average annual precipitation less than 2500mm, these amount is average value of station Alahan Panjang, Surian, and Muaro labuh which each station are differ in the agroclimatic zone, Zone agroclimate C2, D1, and B1 for Alahan Panjang, Surian and Muaro Labuh respectively. The old river terrace of Batang Hari which developed for irrigation scheme has covered the areas on 20000ha conducted areas along the old river terrace of Batang Hari which parts of Siat, Piruko/Palangko, and Mimpi up to the old terrace at cross of the tributary of Jujuhan which main stream. Different elevation between old river terrace with inland areas both Rawa Banto of Sangir and Lake Diateh of Batang Hari is 1300m. Hydrological data of river water discharge by used the value 90% of run off data, which calculate base on the average annual rainfall multiplication by the wide of catchment. These value are not significant different which average 18 years data from 1975-1993 of Automatic Water Level Recording (AWLR). In the value 277m3/det and 284m3/det for average value of AWLR and 90% of runoff value respectively. Compare to the AWLR record in 1975 water discharge is decrease. The data of 1975 is 61% compare to runoff data or 60% compare to average data of AWLR. These indicated that the type of land use of the upper cathment already changed. The amount of discharge has decreases in the value of 40% from the average value as the effect of deforestation during the last 30 years. The hydrological condition also observed at the Siat river. The rate of deforestation could be calculated by using the value of forest contribution to the regional annual budget (PDRB). The validity of the method has needed honesty of the timber company. If the company or government official not fair, for calculation should be used correction factor 50-100 percent. Base on the PDRB data rate of deforestation has calculated in the value of 5000-7000ha/yr. related to the calculation the catchment of Siat, Mimpi, Piruko/Palangko already degraded and Siat river in the dry season especially in August conot open the water intake for irrigation as lack of water discharge. Key words: Rain fall, water discharge, deforestation, and sustainable watershed management